Rare male advantage and sex ratio. - Lechien, J.; Dernoncourt-Sterpin, C.; Elens, A. (Genetica, 1990)
Relative success of mutant white and wild-type CS Drosophila melanogaster males is frequency-dependent, if sex ratio is 1:1. If the number of females is constant, this success depends on the ratio between the mutant and wild-type males. The sex ratio changes strongly affect the male mating activity of both genotypes. Emphasis is placed on the general interest of the Ayala equation and the Wattiaux-Lichtenberger equation in frequency-dependence and sex ratio dependence analysis.